2014
DOI: 10.1371/journal.pone.0110453
|View full text |Cite
|
Sign up to set email alerts
|

A Novel 2.5D Culture Platform to Investigate the Role of Stiffness Gradients on Adhesion-Independent Cell Migration

Abstract: Current studies investigating the role of biophysical cues on cell migration focus on the use of culture platforms with static material parameters. However, migrating cells in vivo often encounter spatial variations in extracellular matrix stiffness. To better understand the effects of stiffness gradients on cell migration, we developed a 2.5D cell culture platform where cells are sandwiched between stiff tissue culture plastic and soft alginate hydrogel. Under these conditions, we observed migration of cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…Researchers have also taken advantage of the ability of hydrogels to swell or shrink in response to external stimuli (e.g., pH, temperature) to develop biosensors for the detection of biomolecules [4,5]. Additionally, their highly porous and hydrated polymer structure mimics the extracellular cellular matrix and renders them highly suitable for in vitro cell culture, and several studies have demonstrated the successful use of hydrogels to encapsulate mammalian cells in a 3D physiological-like environment and develop in vitro models of cell proliferation, migration, and differentiation [6][7][8][9][10]. However, hydrogels have poor mechanical strength, which limits their broad applicability for tissue engineering [11].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also taken advantage of the ability of hydrogels to swell or shrink in response to external stimuli (e.g., pH, temperature) to develop biosensors for the detection of biomolecules [4,5]. Additionally, their highly porous and hydrated polymer structure mimics the extracellular cellular matrix and renders them highly suitable for in vitro cell culture, and several studies have demonstrated the successful use of hydrogels to encapsulate mammalian cells in a 3D physiological-like environment and develop in vitro models of cell proliferation, migration, and differentiation [6][7][8][9][10]. However, hydrogels have poor mechanical strength, which limits their broad applicability for tissue engineering [11].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, 3D encapsulation of cells to preserve their viability during the freeze-thaw cycle opens up the possibility to further increase freezing efficiencies by varying the biophysical and biochemical properties of the scaffold. For instance, recent studies have demonstrated the individual as well as synergistic effects of matrix stiffness and cell-matrix interactions on cell responses to small molecule toxins (Pebworth et al 2014). While it is not clear if the intracellular responses to freeze-thaw and other toxic insults are similar, it could be postulated that biophysical and biochemical properties of the 3D cell culture matrix may also have a significant effect on cell viability during the freeze-thaw process.…”
Section: Comparison With Other Cryoprotectantsmentioning
confidence: 99%
“…(1) various research and bioprocess activities including viral packaging and drug discovery (Dietmair et al 2012), (2) studies where the effects of micro-environmental cues on cell proliferation, transfection and migration are explored (Pebworth et al 2014), (3) in biopharmaceutical production (Bandaranayake and Almo 2014) and (4) in desiccation research for genome mapping against anhydrobiotic organisms to elucidate common protection mechanisms against dehydration at the genetic level (Leprince and Buitink 2010). HEK cells have been cryopreserved using slow freezing in DMSO-based cocktails recommended for cryopreservation (Chaytor et al 2012, Kleman 2008.…”
Section: Introductionmentioning
confidence: 99%
“…To determine whether the RGD-binding site on integrin is required for aMPV/B F protein-mediated membrane fusion, we incubated Vero and BHK-21 cells with RGD peptides that can block integrin as previously described (27,40). As shown in Fig.…”
Section: Peptide Blockade Of Integrin Reduces the Fusogenicity Of Thementioning
confidence: 99%